The management of community development - Hernando, Christine Mae D. (Danyag :the UPV journal of humanities and social sciences, 2009)
"This paper is a synthesis of the Community Development experiences of selected countries in Asia. It presents a historical perspective of CD in various time periods from pre-colonization to present-day CD. It provides significant insights and lessons in the management of CD programs as well as some emerging guidelines in CD in response to problems and issues in CD work and the evolving socio-economic and political issues that challenge the future of Asia's developing communities."